ARSTANBEK - A CLASSICAL OF KYRGYZ ORAL TRADITIONAL MUSICAL AND POETICAL CULTURE (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
In the history of traditional professional oral singing and komuz music, one of our great tokme poets, Arstanbek Buylash uulu, who is known as a horse’s back, occupies a special place, having worked equally in two major fields of national art, on the one hand, tokme poetry, and on the other, komuz music, and has achieved great success. First, as a great singer-poet of that time, he paid attention to the current political and ideological issues of the 19th century (the Ak Tsar Empire, the Kokon Khanate), clearly understood and knew his nomadic social consciousness, and he depicted the life and livelihood of the people in the then popular genres, songs, musical and poetic works, on acute problematic topics, without hesitation, singing to the accompaniment of the komuz he played, without hiding or hiding social events and relations occurring in the people, telling the truth directly, and realistically describing human behavior and vices.
Keywords: Arstanbek, oral traditional professional singing, komuz music, nomadic social consciousness